2017
DOI: 10.1063/1.4982713
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-plane easy-axis in thin films of diluted magnetic semiconductor Ba1−xKx(Zn1−yMny)2As2

Abstract: Single-phased, single-oriented thin films of Mn-doped ZnAs-based diluted magnetic semiconductor (DMS) Ba1−xKx(Zn1−yMny)2As2 (x = 0.03, 0.08; y = 0.15) have been deposited on Si, SrTiO3, LaAlO3, (La,Sr)(Al,Ta)O3, and MgAl2O4 substrates, respectively. Utilizing a combined synthesis and characterization system excluding the air and further optimizing the deposition parameters, high-quality thin films could be obtained and be measured showing that they can keep inactive-in-air up to more than 90 hours characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…These values give an anisotropy field μ 0 H K = 2K U /M sat of 0.85 ± 0.07 T. A positive value of K U means that the easy axis is along the c-axis, which is consistent with a previous study. 17 The obtained m Mn of 0.60 μ B at 20 K is also consistent with a previous study's 6 saturation magnetization (not shown here) but significantly smaller than that of (Ga,Mn)As, 2−4 μ B . 34,35 The cause of the reduction was theoretically attributed to the preferential formation of antiferromagnetically coupled nearest-neighbor Mn pairs 15 but should be clarified experimentally in future studies, for example, by performing XMCD measurements at various temperatures and magnetic fields.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These values give an anisotropy field μ 0 H K = 2K U /M sat of 0.85 ± 0.07 T. A positive value of K U means that the easy axis is along the c-axis, which is consistent with a previous study. 17 The obtained m Mn of 0.60 μ B at 20 K is also consistent with a previous study's 6 saturation magnetization (not shown here) but significantly smaller than that of (Ga,Mn)As, 2−4 μ B . 34,35 The cause of the reduction was theoretically attributed to the preferential formation of antiferromagnetically coupled nearest-neighbor Mn pairs 15 but should be clarified experimentally in future studies, for example, by performing XMCD measurements at various temperatures and magnetic fields.…”
Section: Resultssupporting
confidence: 92%
“…In fact, large perpendicular magnetic anisotropy, where the magnetic easy axis is along the c-axis, was observed by SQUID measurements. 6,17 Perpendicular magnetic anisotropy is useful for future magnetic memory applications because it can lead to a high bit density and reduce the critical current density for magnetization switching. 18 In general, magnetocrystalline anisotropy would not appear from the Mn 2+ high-spin state ( 6 A 1 ) because of the lack of an orbital magnetic moment.…”
Section: Introductionmentioning
confidence: 99%
“…J/m 3 and the saturation magnetization per Mn atom m Mn = 0.60 ± 0.03 µ B . These values give the anisotropy field 2K U /M sat of 0.85 ± 0.07 T. The positive value of K U means that the easy axis is along the c-axis, being consistent with the previous study [17]. The obtained m Mn of 0.60 µ B at 20 K is by far smaller than those of (Ga,Mn)As of 4.5 µ B [4].…”
supporting
confidence: 89%
“…1a), sizable magnetic anisotropy would be expected. In fact, large perpendicular magnetic anisotropy (PMA), where the magnetic easy axis is along the c-axis, was observed by SQUID measurements [6,17], which is useful for future magnetic-memory applications. In general, magneto-crystalline anisotropy would not appear from the Mn 2+ high-spin state ( 6 A 1 ) because of the lack of orbital magnetic moment.…”
mentioning
confidence: 99%
“…Recently a new class of DMS materials has been discoverede.g., Li 1+x (Zn,Mn)As, termed "111-type", and (Ba,K)(Zn,Mn) 2 As 2 , termed "122"in which carrier doping and spin doping are independent from each other, thus overcoming the difficulty just described [15][16][17][18][19][20][21]. For example, in (Ba,K)(Zn,Mn) 2 As 2 the isovalent substitution of Mn 2+ for Zn 2+ enables one to achieve high-Mn solubility (up to ~15% or more) in thermodynamic equilibrium, while substitution of K + for Ba 2+ produces charge carriers (holes) [22,23].…”
Section: Introductionmentioning
confidence: 99%